Longitudinal evaluation of a knowledge translation role in occupational therapy - Danielle Hitch; Kate Lhuede; Lindsay Vernon; Genevieve Pepin; Karen Stagnitti (BMC, 2019)
Abstract Background In 2014, a large metropolitan mental health service in Australia developed a senior role (Lead Research Occupational Therapist) to address an identified need for greater research and knowledge translation, and associated capacity building. The aim of this study was to evaluate the impact, in the first 2.5 years, of this role across a range of variables. Methods Multiple methods were used to gather a comprehensive range of data. Workforce surveys were completed both online and in hard copy in early 2014 (n = 42) and late 2016 (n = 44). Research key performance indicators (academic, research production and cultural) were also identified for measurement over time. The data from these surveys were analysed using descriptive and inductive analysis, and also with social network analysis. Results This role has demonstrated positive outcomes across a range of variables. There was a medium effect on the quantity of participation in quality assurance and knowledge translation activities by the workforce. Most knowledge translation behaviours were occurring regularly, although several were absent. An improving trend in attitudes towards evidence-based practice was recorded, and perceptions of the knowledge translation role were generally positive. The Lead Research Occupational Therapist moved from the periphery to the centre of the evidence based practice social network. Improved awareness of other clinicians deploying evidence based practice was observed, and the frequency of interaction between clinicians increased. The role has met all key performance indicators, across the academic, research production and cultural domains. Conclusions The shift in focus of this role from research to knowledge translation has produced tangible outcomes for the occupational therapy workforce. These achievements have had a positive impact on the sustainability of the role, which will be continued for at least another two years. An ongoing challenge is to directly measure the impact of this role on outcomes for people with mental illness and their carers.